2002
DOI: 10.1002/polb.10326
|View full text |Cite
|
Sign up to set email alerts
|

Microviscosity in poly(ethylene oxide)‐polypropylene oxide‐poly(ethylene oxide) block copolymers probed by fluorescence depolarization kinetics

Abstract: Triblock copolymers [poly(ethylene oxide) (PEO) and polypropylene oxide (PPO)], Pluronic F127 with 100 PEO blocks on each end, and 65 blocks of PPO in the center were examined in aqueous solution. The "sol" and "gel" phase diagram was determined as a function of concentration and temperature. For further study, the concentration was fixed at 20 wt %, and the temperature dependence of the dynamic viscosity differed from the temperature dependence of fluorescence emission spectra and the microviscosity probed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 23 publications
10
53
1
1
Order By: Relevance
“…9,34 In the gel phase, the aqueous solubility of the PEO block (corona region) is diminished, which causes the corona region to shrink. 35 The blue shift of the NpO À * fluorescence maximum in the sol state compared to that in water, and its further blue shift on gelation, thus result from the increase in hydrophobicity of the microheterogeneous organisation of aqueous PF127. The trends in the enhancement of NpOH* fluorescence can View Article Online also be understood by a similar model.…”
Section: Resultsmentioning
confidence: 99%
“…9,34 In the gel phase, the aqueous solubility of the PEO block (corona region) is diminished, which causes the corona region to shrink. 35 The blue shift of the NpO À * fluorescence maximum in the sol state compared to that in water, and its further blue shift on gelation, thus result from the increase in hydrophobicity of the microheterogeneous organisation of aqueous PF127. The trends in the enhancement of NpOH* fluorescence can View Article Online also be understood by a similar model.…”
Section: Resultsmentioning
confidence: 99%
“…4,8,43,72 No sharp change in the anisotropy values around the transition point is in accordance with the anisotropy results of other normal fluorescent probes reported in the literature. [20][21][22]26 With HUF, the r SS values also apparently remain in a similar range (increase only marginally) for the micellar region but indicate a sudden increase for solutions with >25% P123 concentration, indicating the changeover from the micelle to the gel phase. The distinct change in the observed r SS values for HUF around 27-28% P123 is thus attributed to the micelle to gel transition, which is very similar to the reported gelation concentration of P123.…”
Section: Chart 3: Schematic Representation Of the Micelle To Gel Tranmentioning
confidence: 86%
“…Recent excitation wavelength dependent rotational dynamic studies of coumarin 480 (C480) in a micelle as well as in the gel phase of P123 also corroborate the above literature findings. 28,32 However, an increase in one of the components of the reorientation time for the cationic probe rhodamine 123 (Rh123) in 20% aqueous F127 ((EO) 100 -(PO) 65 -(EO) 100 ) solution has been observed by Jeon et al, 22 who ascribed it to the micelle-micelle entanglement above the sol-gel transition temperature. Mali et al 26 showed later that the above observation is actually due to the unimer to micelle transition rather than the sol to gel transition, as initially suggested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micellization studies of such block copolymers provide valuable information regarding the size and morphology of the micelles, as well as the nature of the micellar interior [11]. Although several techniques are available to study the micellization, fluorescence probing is one of the most important methods available, particularly due to its ability to monitor the local environment in close vicinity of the micelle-bound probe molecule [12,13]. Fig.…”
Section: Steady-state Spectroscopymentioning
confidence: 99%